Evaluasi Pengelolaan Keuangan Sekolah Berdasarkan PSAK 45 - Kristin Ninta Ginting; Yayuk Nurjanah (Jurnal Aplikasi Bisnis Kesatuan, 2022)
Evaluation is the process of describing, obtaining, and presenting useful information to formulate an alternative decision. Evaluation is part of the management system, namely planning, organization, implementation, monitoring and evaluation. Financial management is planning, controlling, organizing, controlling resources related to funds so that the goals of an organization can be achieved. Financial management is very important because without financial management, finances cannot run properly and smoothly. Statement of Financial Accounting Standards (PSAK) No. 45 on Financial Reporting of Non-Profit Organizations. Non-profit organizations are usually engaged in services by providing services to the community. The forms of service also vary from education, health to religion. The objectives of this discussion are: (1) knowing financial management at Kosgoro High School, (2) knowing the financial reports at Kosgoro High School, Bogor City, (3) knowing whether the financial reports at Kosgoro High School Bogor City are in accordance with PSAK 45. The results of this discussion indicate that the financial management at SMA Kosgoro is in accordance with PSAK 45 but has not been fully realized according to the recommendations of PSAK 45. Keywords: Evaluation, financial management, PSAK 45